(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2026)
The rapid expansion of urban development in tropical regions has substantially increased local microclimate temperatures, primarily as a consequence of the urban heat island (UHI) phenomenon. Landscape design is widely acknowledged as an effective passive strategy for mitigating these adverse thermal conditions. This study aims to assess the effectiveness of landscape layout and design at the Sheikh Zayed Mosque in Surakarta in reducing both surface and ambient air temperatures within the surrounding neighborhood. The research adopts a quantitative methodological approach that integrates systematic temperature measurements, direct field observations, and an in-depth review of relevant literature. The investigation was carried out through the combined use of satellite imagery, in situ surface temperature measurements, and spatial analysis focusing on the distribution of vegetation, water ponds, and shading elements. The findings demonstrate that the strategic placement of vegetation and water features is capable of reducing surface temperatures by up to 5°C during daylight hours. These results underscore the critical role of landscape design as a climate-adaptive component in public building environments, particularly within tropical contexts. Moreover, the research provides a meaningful contribution to the development of tropical climate-responsive landscape design strategies aimed at enhancing building thermal comfort and supporting the realization of sustainable development in religious public spaces.